Sagot :
One method is to write the function f(x) as y = …….
Then f inverse (let’s call it g(x)) is found by swapping x and y in your equation, then solving for y.
For example: f(x) = ln(2x +3), so y = ln(2x+3)
for g(x), x = ln(2y + 3)
so e^x = 2y + 3
e^x - 3 = 2y
(e^x - 3)/2 = y
so g(x) = (e^x - 3)/2 and f(x) and g(x) are inverse functions.
Then f inverse (let’s call it g(x)) is found by swapping x and y in your equation, then solving for y.
For example: f(x) = ln(2x +3), so y = ln(2x+3)
for g(x), x = ln(2y + 3)
so e^x = 2y + 3
e^x - 3 = 2y
(e^x - 3)/2 = y
so g(x) = (e^x - 3)/2 and f(x) and g(x) are inverse functions.